Multiple metastases of renal clear cell carcinoma to the organs of the head - Sawicki, Piotr; Kaźmierczak, Wojciech; Burduk, Paweł; Kaźmierczak, Henryk (Contemporary Oncology/Współczesna Onkologia, 2014)
Metastases of renal clear cell carcinoma to the organs of the head are rare. Single cases show that they can appear either shortly after or many years after radical surgery. The diagnosis of this cancer is difficult because of its insidious course; therefore, it is often diagnosed too late. Late diagnosis is associated with a high risk of distant metastases and increased mortality. The paper presents a case of a patient whose kidney tumour was diagnosed during hospitalisation at the Department of Rheumatology. Further diagnosis and surgical treatment were performed in the Department of Urology, where a left-sided nephrectomy was carried out. After two years, the patient was hospitalised in the Department of Otolaryngology due to dysphagia. The patient was subjected to fine-needle biopsy, surgical biopsy, CT, and ultrasound. Metastases of renal clear cell carcinoma were diagnosed based on a histopathological examination and the results of imaging studies. Due to the extent of the tumour, diagnostics were extended to magnetic resonance imaging. The patient was qualified for tracheotomy, cytoreductive surgery, and chemoradiation. The patient was referred for further treatment at the Centre of Oncology in Bydgoszcz.